N-Metil Anilin’den türeyen bazı triazenlerin sentezi ve yapılarının aydınlatılması - Çıkla, Pelin (My University, 2005)
The opinions put forward by Modern Economics, which has been institutionalizing and developing ever since the 18th century, have greatly impressed political systems. The production and consumption relations suggested in the light of the opinions put forward by those economists that were first called classics and the roles the State's mechanism is supposed to play within these relations have in the course of time caused deficiencies in the capitalistic economic order. Yet the incurred crises have required once more that there should amendments in the role of the State. Within these modifications and developments the State has been organized apart from its legal entity and the local administrations as public legal entities have resorted to realizing such activities as they have carried on with a view to providing the local people with their necessaries in different methods. We here in our study shall try to explain what kind of changes have occurred in local commodities and services as well as in the presentation of local commodities and services in light of the views suggested by the Capitalistic Economic Order and again the service methods applied at the point reached at the end of these changes. Again, we shall analyze the amendments in the service methods of Istanbul Metropolitan Municipality, which gives local services in the largest metropolitan area in Turkey.
Keywords: Hastalıklar; kan kanseri; Kanserler; Teknoloji (Uygulamalı bilimler); Tıp bilimleri; Tümör; Tümörler ve çeşitli bulaşıcı hastalıklar